Integrating LMX components: How LMX components interactively influence justice and deviance - LIU, Yuchuan (Institutional Knowledge at Singapore Management University, 2019)
Leaders generally differentiate followers, for example, by providing some with more respect, trust, support, or information than others (Liden & Graen, 1980). This differential treatment is a fundamental tenet of leader-member exchange theory (LMX theory). However, the effects of leader differentiation on followers remain inconclusive such that LMX differentiation (LMXD) has negative, positive, or null effects on favorable employee work outcomes across studies (for a recent review, see Martin, Thomas, Legood, & Dello Russo, 2017). One potential reason for those inconclusive findings is that researchers did not consider that leader differentiation inevitably creates varying degrees of relationship quality across leader-follower dyads (LMX quality) and motivates social comparisons among followers as they assess their relative relationship quality with that of their coworkers (LMX social comparison or LMXSC). In this research, we incorporate these three components to theorize and investigate their interactive effects on followers’ supervisory interactional justice perceptions and subsequently on their supervisor-directed deviance. Results from an experiment and a field study support our theoretical model such that when LMX quality and LMXSC are both high, the negative impact of LMXD on followers’ supervisory interactional justice perceptions and its positive indirect effect on supervisor-directed deviance via justice is the weakest (zero).